Morphological and Syntactic Awareness in Poor Comprehenders: Another Piece of the Puzzle. (January 2014) - Tong, Xiuli; Deacon, S. Hélène; Cain, Kate
Poor comprehenders have intact word-reading skills but struggle specifically with understanding what they read. We investigated whether two metalinguistic skills, morphological and syntactic awareness, are specifically related to poor reading comprehension by including separate and combined measures of each. We identified poor comprehenders ( n = 15) and average comprehenders ( n = 15) in Grade 4 who were matched on word-reading accuracy and speed, vocabulary, nonverbal cognitive ability, and age. The two groups performed comparably on a morphological awareness task that involved both morphological and syntactic cues. However, poor comprehenders performed less well than average comprehenders on a derivational word analogy task in which there was no additional syntactic information, thus tapping only morphological awareness, and also less well on a syntactic awareness task, in which there were no morphological manipulations. Our task and participant-selection process ruled out key nonmetalinguistic sources of influence on these tasks. These findings suggest that the relationships among reading comprehension, morphological awareness, and syntactic awareness depend on the tasks used to measure the latter two. Future research needs to identify precisely in which ways these metalinguistic difficulties connect to challenges with reading comprehension.